2010
DOI: 10.1093/alcalc/agq037
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Bone Turnover Markers and Cytokines in Alcohol-Induced Cirrhosis

Abstract: There is a relation between activation of the cellular immunity and osteoporosis in AC. Bone mass loss could be related to the increased bone resorption found in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 27 publications
3
35
0
4
Order By: Relevance
“…Serum parathyroid hormone (PTH) levels are frequently normal 7,9,10,20 despite serum calcium levels being in the lower limit of the normal range or even decreased. However, in disagreement with the presence of a low turnover osteoporosis, but in accordance with some other studies 31 , we found increased serum telopeptide levels among 90 alcoholics, including noncirrhotic ones, (0.53 ± 0.27 ng/ml) compared with controls (Z = 4.00; p < 0.001; Figure 1c), suggesting increased bone resorption. Bone resorption depends on differentiation and activation of osteoclasts, a process which involves binding of receptor activator of nuclear factor kappa b (RANK) ligand (RANK-L) to RANK, expressed in pre-osteclasts cell memAlcohol exerts a double effect on hypothalamic-hypophyseal-gonadal axis 22 , leading to hypogonadism and decreased testosterone levels.…”
Section: Increased Breakdown: Cytokines and The Opg/rank-l Systemsupporting
confidence: 83%
See 1 more Smart Citation
“…Serum parathyroid hormone (PTH) levels are frequently normal 7,9,10,20 despite serum calcium levels being in the lower limit of the normal range or even decreased. However, in disagreement with the presence of a low turnover osteoporosis, but in accordance with some other studies 31 , we found increased serum telopeptide levels among 90 alcoholics, including noncirrhotic ones, (0.53 ± 0.27 ng/ml) compared with controls (Z = 4.00; p < 0.001; Figure 1c), suggesting increased bone resorption. Bone resorption depends on differentiation and activation of osteoclasts, a process which involves binding of receptor activator of nuclear factor kappa b (RANK) ligand (RANK-L) to RANK, expressed in pre-osteclasts cell memAlcohol exerts a double effect on hypothalamic-hypophyseal-gonadal axis 22 , leading to hypogonadism and decreased testosterone levels.…”
Section: Increased Breakdown: Cytokines and The Opg/rank-l Systemsupporting
confidence: 83%
“…Some authors have reported increased breakdown in alcoholic cirrhosis -although not in Child A cirrhotics 31 , whereas in other studies bone resorption was not significantly altered or even reduced 14 . Serum parathyroid hormone (PTH) levels are frequently normal 7,9,10,20 despite serum calcium levels being in the lower limit of the normal range or even decreased.…”
Section: Increased Breakdown: Cytokines and The Opg/rank-l Systemmentioning
confidence: 87%
“…Strongest was the association between hyponatremia and liver insufficiency, which is also known to negatively impact bone metabolism, seemingly irreversible despite liver transplantation for end-stage liver disease [27][28][29][30]. Several markers of protein synthesis, clotting factor production, and cholestasis were significantly altered in hyponatremic patients, i.e., elevated levels of ALAT, bilirubin count, cobalamin, GGT, and APTT, while albumin levels were significantly lower.…”
Section: Hyponatremia As a Marker Of Secondary Osteoporosismentioning
confidence: 99%
“…Epidemiological studies in alcoholics of both genders report significant decreases in bone mineral density (BMD) and increased bone fractures and osteoporosis risk compared with nondrinkers (Clark et al, 2003;Malik et al, 2009;Pasoto et al, 2011;Wuermser et al, 2011), which is related to changes in bone turnover, particularly decreased bone formation and increased bone resorption (Dai et al, 2000;Alvisa-Negrín et al, 2009;Callaci et al, 2010;Díez-Ruiz et al, 2010). Previously, we have reported significant decreases in tibial and femoral BMD after chronic ethanol (EtOH) consumption in cycling female rats receiving isocaloric diets via intragastric infusion [total enteral nutrition (TEN)] Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%